Isolation, Characterization and Genetic Linkage Mapping of Microsatellite Markers in Mystus Nemurus - Hoh, Boon Peng (2005)
The river catfish (Mystus nemurus) is of great potential importance as an alternative fish protein source, notably in Malaysia and Thailand. The seed supply is seasonal and inability to reproduce in captivity is a hindrance to mass produce this species. Molecular breeding and genetic mapping with the use of DNA based markers have paved ways in overcoming conventional breeding to improve important economic traits. The main objectives of this study were to isolate and develop microsatellite markers for Mystus nemurus, and apply these markers on genetic linkage map for this species. Two methodologies were used to isolate the microsatellite loci in M. nemurus, namely Random Amplified Hybridizing Microsatellites (RAHMs) and 5' anchored Polymerase Chain Reaction (5' anchored PCR). A total of 236 repeat sequences were identified. Of these, 13 were developed fiom RAHMs and 223 were developed from 5' anchored PCR.A total of 177 primer pairs were developed. Of these 64 have been screened for polymorphisms on 90 unrelated fishes collected from six locations (Kedah, Selangor, Perak, Johor, Terengganu and Sarawak), where each location consisted of 15 individuals. Forty four primer pairs were found to be polymorphic. The highest heterozygous marker was MnBp5-1-12a (0.871 4) while the lowest heterozygosity was observed in MnBp8-1-25a (0.0000). A dendrogram was constructed from the 44 polymorphic loci. An additional 34 polymorphic markers, previously generated, were combined in order to construct another dendrogram, and it was found that the dendrograrn stabilized at 50 polymorphic microsatellite loci. Induced breeding was carried out to generate two known fish family groupings. The first family grouping was generated from the parents chosen randomly from the Terengganu broodstock. One hundred progeny were produced. The second family grouping was generated from the male chosen from Terengganu population and the female chosen from Pahang population. Fifty progenies were used for the analysis of Mendelian segregation and linkage mapping. A total of 70 microsatellite markers isolated for this species were screened and evaluated for the Mendelian Inheritance ratio on the two fish families, mentioned of which 31 showed segregation in either one of the families. These markers were analyzed with contingency chi-square analysis. Of these, 13 pair markers were grouped into 8 groups. Strategy "Pseudo-testcross" was applied in the linkage mapping analysis. Analysis of linkage using LOD score was carried out and a total of 7 linkage groups were generated from the 2 fish families under the LOD of 1.2. Additional analysis of LOD was performed on the family data of 44 dominant markers done previously. Three linkage groups were obtained at the LOD of 1.2 and fractionated into 6 groups when the LOD score was increased to 2.0. This is the first map generated for M. nemurus which provides information on genetic linkage for this species. It is a stepping-stone for carrying out more intensive genetic mapping and QTL analysis on this species in the future. Eventually, marker assisted selection (MAS) or isolation of economically important genes could be made possible and these would benefit the Malaysian aquaculture industry